Kinematic analysis of CPM machine supporting to rehabilitation process after surgical knee arthroscopy and arthroplasty - Trochimczuk, Roman; Kuźmierowski, Tomasz (Zielona Góra: Uniwersytet Zielonogórski)
Existing commercial solutions of the CPM (Continuous Passive Motion) machines are described in the paper. Based on the analysis of existing solutions we present our conceptual solution to support the process of rehabilitation of the knee joint which is necessary after arthroscopic surgery. For a given novel structure we analyze and present proprietary algorithms and the computer application to simulate the operation of our PCM device. In addition, we suggest directions for further research.
Keywords: rehabilitation; CPM machine; kinematic analysis; arthroscopy; arthroplasty; four bar linkage mechanism; crank-slider mechanism